iPhone 4 : portable genius - McFedries, Paul (Portable genius, 2010)
A handy, quick-access guide to getting the most out of the iPhone 4 If you love all the great stuff that makes up the Apple digital lifestyle, you no doubt consider your iPhone 4 to be indispensable. The newest edition of iPhone Portable Genius is packed with the information you need to make this wonderful device even better